ATRAM 2.0: An Improved, Flexible Locus Assembler for NGS Data. (6th May 2018) - Allen, Julie M; LaFrance, Raphael; Folk, Ryan A; Johnson, Kevin P; Guralnick, Robert P
Massive strides have been made in technologies for collecting genome-scale data. However, tools for efficiently and flexibly assembling raw outputs into downstream analytical workflows are still nascent. aTRAM 1.0 was designed to assemble any locus from genome sequencing data but was neither optimized for efficiency nor able to serve as a single toolkit for all assembly needs. We have completely re-implemented aTRAM and redesigned its structure for faster read retrieval while adding a number of key features to improve flexibility and functionality. The software can now (1) assemble single- or paired-end data, (2) utilize both read directions in the database, (3) use an additional de novo assembly module, and (4) leverage new built-in pipelines to automate common workflows in phylogenomics. Owing to reimplementation of databasing strategies, we demonstrate that aTRAM 2.0 is much faster across all applications compared to the previous version.